Energy budget and carbon footprint assessment under diverse nitrogen management modules in mustard (Brassica juncea L.) production under subtropical climate - Vasudev Meena; Mohan Lal Dotaniya; Murli Dhar Meena; Ram Swaroop Jat; Mukesh Kumar Meena; Ram Lal Choudhary; Hari Singh Meena; Bheeru Lal Meena; Prabhu Dayal Meena; Pramod Kumar Rai; Vijay Veer Singh (PLoS ONE, 2025)
In the context of a changing climate, identifying a sustainable food production system that incorporates cleaner technologies with low C-sequestration and minimal energy inputs is crucial for long-term sustainability. The objective of study was to develop an innovative, energy-efficient system for mustard cultivation with reduced carbon footprint and economic viability by optimizing nitrogen (N) management. The experiment included nine nitrogen management strategies plus one unfertilized treatment as control, arranged in a randomized complete block design in three replicates. Results demonstrated that sensor-based nitrogen application using the GreenSeeker (GS) significantly augmented economic yield by 19.3% and 64.5%, and proved more profitable, boosting net monetary returns and benefit-cost ratio by 125.1% & 36.2% and 58.8% & 24.4%, respectively compared to the recommended dose of fertilizer (RDF) and control, and saved 18.7% of nitrogen. The yield of mustard seeds increased significantly, ranging from a minimum of 3.70% (with RDN 75 + foliar spray @ 1.5% KNO₃) to a maximum of 19.31% under the GreenSeeker (GS) treatment. Further, N foliar spray treatments at N 100 level registered for per cent negative changes in N efficiency (−6.90 to −1.46%) over RDF. Nearly half (46.25%) of the total energy consumption was attributed to fertilizer nitrogen, diesel fuel, threshing, and irrigation contributing 17.7%, 11.4%, 9.68%, and 7.40%, respectively. The GS guided N application consumed comparably lowest energy (5.91% less) than RDF. The energy indices viz. energy input (−5.98%), energy output (+7.25%), energy use efficiency (6.51%), energy profitability (5.51), energy productivity (+18%), respectively were achieved higher by precise N administration using sensor based GS. In contrast, the specific energy (1.39 MJ kg -1 ), energy intensiveness, direct and non-renewable energy usage were highest under RDN 100 over RDN 75 in conjunction with FS of different N sources (U, NCU and KNO 3 ). Congruently, human energy profitability was varied from 0.34 to 9.78%, respectively over RDF. Carbon-related metrics showed that RDN 100 produced higher carbon inputs, outputs, net carbon gains, and spatial carbon footprints compared to RDN 75 . However, GS-based management outperformed RDF, with lower carbon input (−8.1%), higher carbon output (+10.9%), greater net carbon gain (+16.5%), and the lowest carbon footprint (0.30 kg CE kg ⁻ ¹) versus RDF 0.39 kg CE kg ⁻ ¹. Furthermore, CO₂ emissions were approximately 81% higher in fertilized plots (1921 kg CO₂-e ha ⁻ ¹) compared to unfertilized ones. Overall, the study concludes that sensor-based precise nitrogen management using GS is an innovative, sustainable, and energy-efficient approach that reduces the carbon footprint, combat climate change, and supports food security.